Legal Analysis of the Increasing Number of Marriage Dispensations in 2020-2022 at the Rantau Prapat Religious Court - Fahmi, Fikri Fadhilah; Ramadani, Ramadani (IHSA Institute, 2024)
This research aims to identify the primary factors driving the increase in marriage dispensation requests at the Rantau Prapat Religious Court from 2020 to 2022 and analyze legal opinions on this phenomenon. The study employs qualitative descriptive analysis, gathering data through in-depth interviews, document analysis, and participant observation. Findings indicate that social and economic changes, the impact of the COVID-19 pandemic, low education levels, and local cultural and traditional influences are significant factors contributing to the rise in marriage dispensation requests. Additionally, the legal analysis reveals that judges exhibit flexibility in applying the law by considering the specific circumstances of each case, ensuring decisions are made in the best interests of the children and families involved.